Upaya Meningkatkan Hasil Belajar Matematika pada Pembelajaran Pecahan Sederhana melalui Media Kartu Pecahan pada Siswa Kelas VI SDN Temon Kecamatan Trowulan Kabupaten Mojokerto Tahun Pelajaran 2018/2019 - Nur Kotib (PROGRESSA: Journal of Islamic Religious Instruction, 2020)
In general, students think that Mathematics is the most difficult subject than other subjects, most students are less interested in mathematics because mathematics is a science related to something abstract, so they are less motivated to learn mathematics. For this reason, it is necessary to have an activity that is concrete, interesting and fun in improving student learning outcomes in learning simple fractions through fraction card media for Grade VI students of SDN Temon, Trowulan District, Mojokerto Regency, 2018/2019 Academic Year. Fraction card media is a learning media that researchers created based on the concept of fractions using fraction cards made of bright colored paper and there are fraction numbers in the form of decimals on the left side and fraction forms that are equivalent to decimal fractions on the right side. The number of fraction cards that the researcher made were 36 cards. This research was conducted in the first semester of the 2018/2019 academic year with classroom action research techniques which were carried out in 2 cycles. Based on the data analysis carried out, it was concluded that in cycle I the percentage of student learning outcomes reached 69% and based on the conversion of the minimum completeness criteria set by SDN Temon, Trowulan District, Mojokerto Regency, the percentage of student learning completeness was in the sufficient category, so it is necessary for researchers to continue research in cycle II. In cycle II the percentage of student learning outcomes showed a significant increase, reaching 91%, so it can be concluded that fraction card media can improve student learning outcomes on simple fraction material.